ANALISIS KEBIJAKAN PEMERINTAH TERHADAP PEKERJA MIGRAN INDONESIA DI MASA PANDEMI COVID-19 (Studi Kasus Pemberangkatan PMI di Masa Pandemi) - Ajeng Tiara Bangga Rahmawati (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Reopening of migrant workers' departures during the covid pandemic presents a contrast to the various protection policies that have been made before. This research aims to answer the research question: